Multiple-antenna systems and multiuser communications: Fundamentals and an overview of software-based modeling techniques. (November 2017) - Sheng, Guo; Wang, Yuxin; Lv, Zhihan; Song, Houbing
Abstract: In this paper, advanced contemporary multiple communication techniques, including multiple-antenna systems and multiuser communications are introduced and analyzed in details. Moreover, their supportive software-based modeling techniques are also detailed with appropriate mathematical derivations and simulations. Additionally, random access methods, as a promising and efficient implementation of multiuser communications are also briefly introduced for industrial use purposes. By reading this paper, the readers are expected to have a broad understanding of these advanced contemporary multiple communication techniques and acquire the technical know-hows of software-based simulation and industrial implementation of these techniques. Meanwhile, this paper is also expected to play the role of a solid reference for the relevant technicians which might require the introduced modeling techniques in this paper.